Ethnicity Strongly Influences Body Fat Distribution Determining Serum Adipokine Profile and Metabolic Derangement in Childhood Obesity - Martos-Moreno, Gabriel Á.; Martínez-Villanueva, Julián; González-Leal, Rocío; Barrios, Vicente; Sirvent, Sara; Hawkins, Federico; Chowen, Julie A.; Argente, Jesús (Frontiers in Pediatrics, 2020)
Background: Body fat content and distribution in childhood is influenced by sex and puberty, but interethnic differences in the percentage and distribution of body fat also exist. The abdominal visceral/subcutaneous fat ratio has been the main feature of body fat distribution found to associate with the serum adipokine profile and metabolic derangement in adulthood obesity. This has also been assumed for childhood obesity despite the known singularities of this disease in the pediatric age in comparison to adults. Objective: We aimed to investigate the effect of ethnicity, together with sex and pubertal status, on body fat content and distribution, serum adipokine profile, metabolic impairment and liver steatosis in children and adolescents with obesity. Patients & Methods: One hundred and fifty children with obesity (50% Caucasians / 50% Latinos; 50% males / 50% females) were studied. Body fat content and distribution were studied by whole body DXA-scan and abdominal magnetic resonance, and their relationships with liver steatosis (as determined by ultrasonography), glycemia, insulinemia, lipid metabolism, uric acid, total and HMW-adiponectin, leptin, leptin-receptor and sex steroid levels were explored. Results: Latino patients had more severe truncal obesity (higher trunk/lower limb fat ratio, odds ratio 10.00; p<0.05) and higher prevalence of liver steatosis than Caucasians regardless of sex or pubertal status, but there were no difference in the visceral/subcutaneous abdominal fat ratio, except for pubertal females. A higher trunk/lower limb fat ratio, but not the visceral/subcutaneous abdominal fat ratio, was associated with adipokine profile impairment (higher free leptin index and lower adiponectin levels), insulin resistance and dyslipidemia, and was further enhanced when liver steatosis was present (p<0.05). A higher abdominal visceral/subcutaneous fat ratio was observed in prepubertal children (p<0.01), except for Latino females, whereas predominant subcutaneous fat deposition was observed in adolescents. Conclusion: Ethnicity is one of the main determinants of increased trunk body fat accumulation in Latino children with obesity, which is best estimated by the trunk/lower limb fat ratio and related to the development of metabolic derangement and liver steatosis.